Family planning (KB) practices and the impact on Papuan women reproductive health - Usman Idris; Simon Abdi K. Frank; Reni F. Hindom; Jumiaty Nurung (Elsevier, 2021)
Objective: This study aims to describe and analyze KB or family planning practices and their impact on Papuan women. A case study was conducted in Waena Village, one of the Kampung KB in Jayapura City, Papua. Methods: The research method used is descriptive qualitative using an ethnographic approach. The determination of the informants was done purposively by assigning one of the key informants. Data collection includes in-depth interviews and observation. Data analysis includes data reduction, data description, and interpretation. Results: The results showed that women of childbearing age carried out the practice of KB by using various forms of birth control. Some use birth control pills and spiral birth control (intrauterine contraception). In addition, the family planning program has provided education to increase knowledge about reproductive health, types of diseases so that women feel more valued and cared for by men with the existence of KB program. Moreover, the existence of the Kampung KB program also has an impact on community social activities, such as educate adolescents and children to have a clean and healthy lifestyle oriented toward family welfare. Conclusion: The Kampung KB program in Waena Village has educated the public about reproductive health, which significantly affects community order.